Do fio da navalha de Wittgenstein : o intangível limite entre a linguagem e a realidade no Tractatus Logico Philosophicus - Macedo, Thiago Andrade (2024)
Our objective, in this investigative work, is to present a critical analysis of the pictorial theory of language, exposed by Ludwig Wittgenstein in the Tractatus logico-philosophicus – a seminal work that marks the first phase of the philosopher's thought and one of the bases for the development of philosophy analysis of language and philosophy of mind in the decades following its publication. The central philosophical problem, in this intricate context, is to establish what the real limit between language and the world would be, clarifying the role that this relationship can have in our understanding of reality. Within this perspective, we will explain the thesis of isomorphism – which aims to establish the limits between language and reality – in the universe of the pictorial theory of language. Following this direction of research, the crucial question to be outlined is whether declarative statements, that is, assertions, are sufficient to portray all reality. We intend to deal with the distinction between saying and showing, from a Tractarian perspective, which serves to demonstrate the mastery of what can be said and the mastery of what can only be shown through language, in addition to commenting on the task of philosophy, proposed by work. In his purpose of delimiting the scope of language, in its relationship with the world, using the logical method, Wittgenstein imposes, in the same way, limits on thought and experience. As a result, aporias and questions arise surrounding the essence of the Tractatus, which we will seek to scrutinize and debate throughout the body of the text. We will attempt to launch critical counterpoints to some of the main theses of the work that deal with the representation of reality through language, pointing out possible gaps, mistakes and contradictions, in addition to comparing different points of view of interpreters and commentators of the book, highlighting its extreme importance for the turning point linguistics and the development of analytical philosophy of language, philosophy of mind, philosophy of science and other areas of knowledge. We will also seek to show the influences received by the work and who it subsequently influenced, comparing it with the second moment of the author's philosophical production. In doing so, this dissertation aims to contribute to a deeper understanding of the interaction between language and reality in Wittgenstein's philosophy.